The Impact of Augmented Reality-Based Learning Media on Students’ Digital Literacy Skills: A Study on Junior High School Students - Risnawati; Ramadan, Mohamed; Baba, Khalib; Hammad, Sali; Rustaminezhad, Mohammad Ali (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: This study examines influence of augmented reality (AR)-based learning media on junior high school students' digital literacy skills, exploring its potential to enhance technology integration in education. Methodology: Conducted in Jambi, the research involved 220 students and employed a mixed-method approach, collecting data through questionnaires that assessed students’ responses to AR use and their digital literacy levels. Data analysis using SPSS 21 included descriptive statistics and regression analysis to evaluate the relationship between AR media and digital literacy development. Main Findings: The findings revealed overwhelmingly positive student perceptions of AR-based learning media, with 58.6% rating it as “Good” and 24.2% as “Very Good.” Additionally, 62.3% of students demonstrated “Good” digital literacy skills, with an average score of 28. Regression analysis indicated a significant relationship between the use of AR learning media and improvements in students' digital literacy, with AR contributing 65.1% to the observed variance. The study further highlighted that AR media fostered interactive and immersive learning experiences, making abstract concepts more accessible and engaging for students. Novelty/Originality of this study: The novelty of this study lies in its focus on the dual impact of AR in promoting both academic learning and essential 21st-century skills like digital literacy. By illustrating the practical benefits of AR in junior high school education, this research offers valuable insights for educators and policymakers aiming to integrate innovative technologies into curricula. These findings underscore AR's potential to transform traditional classrooms, preparing students for a digitally-driven future while enhancing their learning outcomes.